Bismuth acetate by XPS - Rodriguez Pereira, Jhonatan; Rincon-Ortiz, Sergio A; Ospina, Rogelio (American Institute of Physics, 2020)
Bismuth (III) acetate was analyzed using x-ray photoelectron spectroscopy. The specimen is a powder purchased from Sigma Aldrich. The sample was fixed to a stainless-steel sample holder with copper 3M(TM)double-sided adhesive tape. Survey spectra, Bi 4f, O 1s, C 1s, Bi 4d, Bi 5d, Bi 6s core levels, and valence band spectra were acquired. The results showed how the elements in the structure of bismuth acetate are related.
Octan bismutitý analyzovaný pomocí XPS
Keywords: bismuth acetate; XPS; precursor; octan bismutitý; XPS; prekurzor